Epidemiology of Drug Resistant Tuberculosis in Samtse General Hospital, Bhutan: A Retrospective Study (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2019)
Introduction: Multidrug resistant tuberculosis (MDR-TB) is defined as a case of tuberculosis resistant to rifampicin and isoniazid which are the first line anti tuberculosis drugs. Globally emergences of MDR-TB possess a challenge to TB control. In Bhutan, the proportion of MDR-TB is high at par with the global level. This study will explore the predictors of MDR-TB and the trend at Samtse General Hospital which has high burden of tuberculosis.Methods: This was a retrospective cross sectional study. The data was extracted from TB treatment cards maintained at TB unit of Samtse General Hospital TB from January 2012 to June 2018.Results: The study showed the prevalence of drug resistant to at least one drug at 21% and MDR-TB prevalence at 16%. The patients with previous treatments (AOR: 4.59; 95% CI .03-.18) and patients under the age of 30 years (AOR: 2.7; 95% CI 1.01- 7.42) were significantly associated with MDR-TB.Conclusion: This study shows high prevalence of MDR-TB in Samtse. Better strategies and concrete actions need to be developed to combat the increase of MDR-TB.